COMPLETE CROSS-SECTIONAL ANALYSIS OF HOTEL BUSINESS TERMS IN ENGLISH AND UZBEK LANGUAGES - Laylo MIRZOEVA (Scholar Express Journal, 2024)
This article is about a complete cross-reference analysis of hotel business terms in English and Uzbek languages. In addition, the history of hospitality is the study of consumer and material and cultural services related to hospitality
Keywords: Hotel; business; motel